Marketing management : text and cases - Czinkota, Michael R. (Blackwell, 1997)
THis boook presents: An Overview of Marketing; Understanding the Buyer, the Environment and the Competition; marketing Planning; Marketing Research and Information; Forecasting; market Segmentation, Positioning and Branding; Product and Service Decisions; New Products; Pricing Decisions; Distribution Decisions; Designing Effective Promotion and Advertising Strategies; Direct Marketing, Sales Promotion, and Public Relations; Selling and Sales Management; and The Future of Marketing.